Strain of Synechocystis PCC 6803 with Aberrant Assembly of Photosystem II Contains Tandem Duplication of a Large Chromosomal Region - Tichý, Martin; Bečková, Martina; Kopečná, Jana; Noda, Judith; Sobotka, Roman; Komenda, Josef (Frontiers in Plant Science, 2016)
Cyanobacterium Synechocystis PCC 6803 represents a favored model organism for photosynthetic studies. Its easy transformability allowed construction of a vast number of Synechocystis mutants including many photosynthetically incompetent ones. However, it became clear that there is already a spectrum of Synechocystis ‘wild-type’ substrains with apparently different phenotypes. Here we analyzed organization of photosynthetic membrane complexes in a standard motile Pasteur collection strain termed PCC and two non-motile glucose-tolerant substrains (named here GT-P and GT-W) previously used as genetic backgrounds for construction of many photosynthetic site directed mutants. Although both the GT-P and GT-W strains were derived from the same strain constructed and described by Williams in 1988, only GT-P was similar in pigmentation and in the compositions of Photosystem II (PSII) and Photosystem I (PSI) complexes to PCC. In contrast, GT-W contained much more carotenoids but significantly less chlorophyll (Chl), which was reflected by lower level of dimeric PSII and especially trimeric PSI. We found that GT-W was deficient in Chl biosynthesis and contained unusually high level of unassembled D1-D2 reaction center, CP47 and especially CP43. Another specific feature of GT-W was a several fold increase in thelevel of the Ycf39-Hlip complex previously postulated to participate in the recycling of Chl molecules. Genome re-sequencing revealed that the phenotype of GT-W is related to the tandem duplication of a large region of the chromosome that contains 100 genes including ones encoding D1, Psb28 and other PSII-related proteins as well as Mg-protoporphyrin methylester cyclase (Cycl). Interestingly, the duplication was completely eliminated after keeping GT-W cells on agar plates under photoautotrophic conditions for several months. The GT-W strain without a duplication showed no obvious defects in PSII assembly and resembled the GT-P substrain. Although we do not exactly know how the duplication affected the GT-W phenotype, we hypothesize that changed stoichiometry of protein components of PSII and Chl biosynthetic machinery encoded by the duplicated region impaired proper assembly and functioning of these multisubunit complexes. The study also emphasizes the crucial importance of a proper control strain for evaluating Synechocystis mutants.